Morphologic study of liver and pancreatic parenchyma in conditions of L-arginine-induced acute pancreatitis. - Sirenko, O. Yu.; Tverdokhlib, I. V.; Stepanov, Yu. M. (Морфологія / Morphologia / Morfologìâ, 2011)
The purpose of current study was to define the role of hepatic mircocirculation in development of pathomorphological changes in liver after the onset of acute pancreatitis in rats. To induce acute pancreatitis intraperitoneal injection of 3 g/kg, 4 g/kg and 5 g/kg of L-arginine was used. It is one of the most reproducible ways to model acute pancreatitis. So far explanations of the pathogenesis of arginine-induced pancreatitis were controversial, although most authors associate cytotoxic / cytostatic effects of NO synthesis from arginine which further interacts with superoxide radicals producing peroxynitrite, resulting in oxidative stress and arginine-based change in the level of neurotransmitters. We have studied of pancreas and liver were carried out in. Following 1, 4, 8, 12, 24, 48 and 72 hours after the injection pancreatic and liver tissues were taken for basic histologic study. Substantial changes in hepatic mircocirculation in modeled acute pancreatitis was found to depend on the pathomorphological changes in pancreas. This reaction proceeds in phases: 1) activation of hepatic circulation, which dominates in portal component, while the pancreatic enzyme toxemia occurs; 2) development of inflammatory, dystrophic, destructive and necrotic changes in hepatic tissue in combination with mircocirculation disorders, simultaneously with the pancreatic necrotic toxemia; 3) adoptive recovery or decompensation processes in mircocirculation system of liver and hepatic parenchyme, which depends on the level of pancreatogenic toxemia|.